Personality traits and work performance of paddy farmers in the Central River Region, Gambia - Demba, Sanyang (2017)
The local rice production in tidal areas has recently reached production crisis as the performance of local paddy farmers is declining. The average production of paddy rice in the Gambia is below 1.5 Mt/ha in the irrigated fields, although records showed that initial yields during the first years of production averaged above 5 Mt/ha. However, the major causes of yield reduction often cited include farmers’ attitude which have never been deliberated in the area. The study aims to determine the level of personality traits of paddy farmers, to examine relationship between personality traits and work performance, and to identify the strength of the traits relationship with work performance for paddy farmers in Central River Region, The Gambia. This research used quantitative research method. The questionnaires were analyzed and correlation and regression coefficient analysis procedures were used. Seven independent variables and a dependent variable were identified. Stratified randomized method was used to meet the 300 paddy farmers from nine rice production perimeters. Results reveal two levels among personality traits; high (decision making, investment, discipline) and moderate (information seeker, risk taking, networking and problem solving). The seven personality traits all have positive correlation with work performance. The interpretation reads improvement of farmers personality traits will lead to better work performance and will probably improve production performance. However, two level of strength relationship, discipline, networking, problem solving, risk taking, and information seeking have moderate correlation (0.41< 0.70), whilst, investment and decision making have weak correlation (0.21< 0.40). The level of personality traits of paddy farmers in CRR highlighted moderate dominant, there is a positive correlation between personality traits and work performance. Respondents’ estimate coefficients performance model highlighted the significance of five personality traits to paddy farmers’ work performance as shown by the score, Adj.R2 of 58.5%. Discipline was identified as the most contributing personality traits that influence paddy farmers’ work performance. This study contributes to a better understanding of the relationship of personality traits to work performance, personality traits are genuinely important for any meaningful improvement in rice production.